Spatiotemporal evaluation and analysis of cultivated land ecological security based on the DPSIR model in Enshi autonomous prefecture, China - He, Nan; Zhou, Yong; Wang, Li; Li, Qing; Zuo, Qian; Liu, Jingyi; Li, Mengyao (Ecological indicators, 2022)
•A comprehensive evaluation index system for cultivated land ecological security (ES) was constructed.•The spatiotemporal patterns of cultivated land ES in Enshi Autonomous Prefecture were assessed from 2005 to 2018.•The overall cultivated land ES has improved, and its main obstacle factors have changed over time.•Policy implications for maintaining cultivated land ES were proposed. Evaluating and analyzing cultivated land ecological security (ES) can reliably optimize ecosystem service supplies in cultivated lands. This study selected Enshi Autonomous Prefecture (Enshi Prefecture) as the research area, aiming to assess the spatiotemporal variability of cultivated land ES level and analyze its main obstacle factors, thus providing paths for its enhancement. Based on the driving force-pressure-state-impact-response (DPSIR) model framework, an index system for evaluating cultivated land ES was constructed. Then, the index weights were calculated by the entropy method, and a comprehensive index of ES was calculated by the composite index method to determine its security level. Finally, the main obstacles affecting cultivated land ES were analyzed by the obstacle degree model. The results showed that (1) From 2005 to 2018, the ES composite index rose from 0.402 to 0.685. The ES level went through a relatively insecure stage (2005–2012), generally secure stage (2013–2016) and relatively secure stage (2017–2018). (2) Regional differences in the cultivated land ES level are obvious, with lower ES in the eastern and western regions than in the central region in 2005 and lower ES in the eastern region than in the central and western regions in 2010 and 2018. (3) The main obstacles affecting cultivated land ES underwent significant temporal changes. From 2005 to 2009, they included the proportion of environmental investment in gross domestic product (GDP), effective irrigation area ratio, and per-capita GDP; in 2010–2018, they included the population density, fertilizer application per cultivated land area unit, and share of primary industry to GDP. Compared with the main obstacles of 2005, those of 2018 demonstrated a significantly larger magnitude. This study improves the understanding of cultivated land ES and its obstacle factors, which supports the sustainable use of cultivated land resources and the protection of the trinity of quantity-quality-ecology in Enshi Prefecture and similar regions.